Pelatihan penguatan literasi dasar penumpang transportasi umum (Bus Si Mas Ganteng) rute Bojonegoro – Tuban - Putri, Siti Nur Aisya (Penamas: Journal of Community Service, 2025)
Public transportation in Tuban Regency, known as Bus Si Mas Ganteng, officially operates on the Bojonegoro–Tuban route and has attracted strong enthusiasm from the community, particularly children and mothers. The bus service is free of charge and features clean facilities, air conditioning, a distinctive design, and a focus on passenger comfort and safety. These conditions provide a strategic opportunity to implement basic literacy training during travel. The purpose of this community engagement program is to foster passengers’ reading interest through interactive literacy approaches in public transportation. The methods employed include structured training, 30-minute reading practice sessions, and activities designed to promote reading with enjoyment. The results show that the literacy training successfully engaged 10 child passengers and three adult passengers. Participants demonstrated an understanding of the importance of literacy and expressed a commitment to applying it in daily life. Passengers were encouraged to read for at least 30 minutes, participate in discussions, and receive guidance from lecturers and students. In addition, the team contributed 20 books as a collection for Bus Si Mas Ganteng. This activity demonstrates that public transportation can serve as an educational space to foster a literacy culture and encourage communities to develop sustainable reading habits.